2011
DOI: 10.1093/jac/dkr272
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 2B6 (CYP2B6) and constitutive androstane receptor (CAR) polymorphisms are associated with early discontinuation of efavirenz-containing regimens

Abstract: These data indicate that genetic variability in CYP2B6 and CAR contributes to early treatment discontinuation for efavirenz-based antiretroviral regimens. Further studies are now required to define the clinical utility of these associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 38 publications
(21 reference statements)
8
52
1
Order By: Relevance
“…Citation with higher plasma EFV concentrations and its toxicity, which could result in an early discontinuation of antiretroviral therapy [16][17][18]. These values are similar to the results of Uttayamakul et al (38.46%, 47.69%, 13.85%) [19].…”
Section: Cyp 2b6 Genetic Variationssupporting
confidence: 76%
“…Citation with higher plasma EFV concentrations and its toxicity, which could result in an early discontinuation of antiretroviral therapy [16][17][18]. These values are similar to the results of Uttayamakul et al (38.46%, 47.69%, 13.85%) [19].…”
Section: Cyp 2b6 Genetic Variationssupporting
confidence: 76%
“…[69,70] In a limited sample size study CYP2B6 slow metabolizing children had higher CSF nevirapine concentrations than fast metabolizers. [71] In the aforementioned study on darunavir CSF concentrations a borderline association was found between polymorphisms in the SLCO1A2 gene (encoding for OAT1A2) and CSF concentrations.…”
Section: Transporters and Pharmacogeneticsmentioning
confidence: 99%
“…Higher rates of neuropsychiatric disorders in patients of African origin have been reported to be linked with the increased serum levels of efavirenz [8,9]. It is postulated that the defective CYP2B6 G516T variant allele, which is common in African population, impairs the efavirenz metabolism, thus increasing the efavirenz plasma concentrations, thereby leading to toxicity [10,11].…”
Section: Introductionmentioning
confidence: 99%